Posterior Reversible Encephalopathy Syndrome Caused by Fioricet (Butalbital-Acetaminophen-Caffeine) - Naomi Cret; Madalina Halalau; Shahab Rezvani; Alexandra Halalau (Case Reports in Medicine)
A common side effect of Fioricet (butalbital-acetaminophen-caffeine) is high blood pressure caused by the caffeine content. We report a case of a 54-year-old female who developed the worst headache of her life after taking 2 tablets of butalbital-acetaminophen-caffeine every six hours for three days before presenting to the emergency department, where her blood pressure was 178/87 mmHg. A brain MRI showed edema in the subcortical white matter of the right occipital lobe, right parietal lobe, and left occipital lobe. Posterior reversible encephalopathy syndrome (PRES) was diagnosed. The patient returned within the week with severe headaches, visual hallucinations, and a blood pressure of 150/80 mmHg. Repeat brain MRI showed slight improvement of edema. Her brain imaging studies completely normalized at 10 months after diagnosis. Although the patient received appropriate treatment, she was unable to make full recovery. Due to her inability to work and the constant pain, the patient continues to struggle with depression.